Demonstrating a positive return on investment for a prenatal program at a managed care organization: an economic analysis. - Sackett K; Pope RK; Erdley WS (Journal of Perinatal & Neonatal Nursing)
Healthcare providers need information to guide the management of patient health while administrators focus on resource management. The underpinning of economic analysis, in the clinical setting, is that resources are scarce. The allocation of resources requires delivered services to provide more benefits than cost and hence, the need to demonstrate a return on investment (ROI) for disease management programs. This article describes the ROI for a prenatal program developed at a Western New York Managed Care Organization (MCO). A positive ROI for the program under study will be demonstrated using a model of economic analysis.